Street Children and its Impact on Educational Attainment in North-Western State (Punjab) of Pakistan - Vedadi, Somaiyeh; ., Syed Muhammad Javed Iqbal; ., Saqib Muneer (Journal of Education and Vocational Research, 2013)
Street children constitute a violent category in most societies; they have considered what society considers appropriate relationships with major institutions of childhood such as family, education and health. The study sets to examine background characteristics of street children, surviving strategies of street children, abuse experienced by street children, problems encountered on the street. The sample of 250 respondents was selected by simple random sampling technique through well-structured questionnaire. The instrument comprised on two sections. According to the results of the study the neglect is most common abuse experienced by children in the selected area of study and it is increasing highly. In addition, it was discovered that socio-economic status serves as a predictor to existence of street children in country i.e. as the age increases, level of abuse also increases. Therefore, the study recommends that a better social supports for children, the need to establish street rehabilitation strategy to come-in to serve as a very effective way to support street children as it occurs at locations where they live.